EFL students’ experiences with audio-based authentic materials in extensive listening - Diva Zahra Anindya; Endang Darsih; Asty Widyastuti (Cipta Pustaka Nusantara, 2026)
This study explores English Education students’ perceptions and experiences in using audio-based authentic materials, particularly real-life announcements, in an Extensive Listening context at Universitas Kuningan. Using a qualitative approach, data were collected through semi-structured interviews with five participants and analyzed using thematic analysis. The findings indicate that authentic materials create a dynamic learning experience shaped by the interplay between motivation, cognitive engagement, and linguistic challenges. Students perceive authentic input as engaging and relevant to real-world communication, enhancing their motivation and sense of readiness. However, features such as rapid speech, background noise, and unfamiliar vocabulary increase cognitive load and may hinder comprehension. Despite these challenges, students employ adaptive strategies including visualization and top-down processing to construct meaning. These findings suggest that authenticity should not be viewed as inherently beneficial, but as a pedagogical resource whose effectiveness depends on balancing challenge and learner readiness. The study highlights the importance of scaffolding strategies to optimize the use of authentic materials in EFL listening instruction.